Longevity the Ultimate Risk for Ageing Populations, says John Piggott - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
The proportion of elderly people in the population is increasing with Japan leading the field globally. The long-run effect is to put an increased burden on the young to support them. John Piggott, research dean at the Australian School of Business, University of New South Wales, spoke on longevity as the ultimate risk in the 21st Century at a seminar organised by the Sim Kee Boon Institute for Financial Economics at the Singapore Management University at the end of last year.